1998
DOI: 10.1016/s0092-8674(00)81765-1
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila Gene hid Is a Direct Molecular Target of Ras-Dependent Survival Signaling

Abstract: Extracellular growth factors are required for the survival of most animal cells. They often signal through the activation of the Ras pathway. However, the molecular mechanisms by which Ras signaling inhibits the intrinsic cell death machinery are not well understood. Here, we present evidence that in Drosophila, activation of the Ras pathway specifically inhibits the proapoptotic activity of the gene head involution defective (hid). By using transgenic animals and cultured cells, we show that MAPK phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
408
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(432 citation statements)
references
References 57 publications
21
408
2
1
Order By: Relevance
“…The Ras-MAPK pathway has been shown to promote cell survival in many di erent systems (Xia et al, 1995;Gardner and Johnson, 1996;Parrizas et al, 1997;Kurada and White, 1998;Bergmann et al, 1998). There has been a lack of functional connection between the Ras-MAPK pathway and a pro-apoptotic molecule or death antagonist of the BCL-2 family although the Ras-MAPK pathway has been shown to down-regulate the proapoptotic activity of the gene head involution defective (hid) (Kurada and White, 1998;Bergmann et al, 1998). Our results suggest that BAD may not only provide a relay for the antiapoptotic activity of Akt, but also act as a potential e ector for MAPKmediated suppression of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ras-MAPK pathway has been shown to promote cell survival in many di erent systems (Xia et al, 1995;Gardner and Johnson, 1996;Parrizas et al, 1997;Kurada and White, 1998;Bergmann et al, 1998). There has been a lack of functional connection between the Ras-MAPK pathway and a pro-apoptotic molecule or death antagonist of the BCL-2 family although the Ras-MAPK pathway has been shown to down-regulate the proapoptotic activity of the gene head involution defective (hid) (Kurada and White, 1998;Bergmann et al, 1998). Our results suggest that BAD may not only provide a relay for the antiapoptotic activity of Akt, but also act as a potential e ector for MAPKmediated suppression of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The Ras-MAPK signaling pathway is essential for cell proliferation and differentiation (Cowley et al, 1994). It also plays an important role in the regulation of cell survival (Xia et al, 1995;Gardner and Johnson, 1996;Parrizas et al, 1997;Bergmann et al, 1998). MAPK activity was examined in HEK293 cells stimulated with EGF, IGF-I or insulin using a phospho-speci®c antibody and by means of gel-mobility shift assays.…”
Section: Bad Phosphorylation At Ser-112 Correlates With Activation Ofmentioning
confidence: 99%
“…According to this hypothesis, the primary function of EGFR during ommatidial assembly might be to prevent apoptosis, thereby allowing cells to adopt appropriate cell fates in response to other signaling cues. Supporting this idea, it is well established that EGFR signaling inhibits apoptosis in the eye (Bergmann et al, 1998;Kurada and White, 1998;Baker and Yu, 2001). For example, no cells from Egfr null clones survive to adulthood, pre-sumably because these clones undergo extensive programmed cell death soon after the MF has passed (Xu and Rubin, 1993;Dominguez et al, 1998).…”
Section: Egfr Signaling Is Required For All Eye Cell Fates Except R8:mentioning
confidence: 91%
“…Several laboratories have demonstrated that signaling from the Drosophila epidermal growth factor receptor (dEgfr/ DER/Torpedo/Flb)/ras pathway promotes lattice cell life, [13][14][15][16] in part through negative regulation of the cell death effector head involution defective (HID). 17,18 During the period of lattice cell death, dEgfr is expressed by all lattice cells, and its soluble ligand, Spitz (Spi), is expressed by cone cells and primary pigment cells. 13 Counteracting the dEgfr/ras pathway is the Notch signaling pathway that directs lattice cell death.…”
mentioning
confidence: 99%